2015
DOI: 10.1016/j.actbio.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic response of cell invasion to matrix stiffness in three-dimensional biopolymer networks

Abstract: When cells come in contact with an adhesive matrix, they begin to spread and migrate with a speed that depends on the stiffness of the extracellular matrix. On a flat surface, migration speed decreases with matrix stiffness mainly due to an increased stability of focal adhesions. In a 3-dimensional (3D) environment, cell migration is thought to be additionally impaired by the steric hindrance imposed by the surrounding matrix. For porous 3D biopolymer networks such as collagen gels, however, the effect of matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 46 publications
6
93
1
Order By: Relevance
“…These key findings are also in agreement with the behavior observed in previous experimental studies (17). For example, Lang et al (17) used glutaraldehyde to enhance the stiffness of the gel, while maintaining the concentration of the ligands.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These key findings are also in agreement with the behavior observed in previous experimental studies (17). For example, Lang et al (17) used glutaraldehyde to enhance the stiffness of the gel, while maintaining the concentration of the ligands.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Lang et al (17) used glutaraldehyde to enhance the stiffness of the gel, while maintaining the concentration of the ligands. They showed that adding glutaraldehyde to collagen matrices with dilute concentration of collagen, increases the cell invasion, suggesting that the stiffness of the matrix promotes cell invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains difficult to decouple the effects of fiber diameter, pore size and biomechanics, but it appears that all three act on cells (reviewed in [88]). For example, crosslinking and crosslinking density each affect cell invasion, with a significant interaction, such that crosslinking loose ECM environments increased invasiveness, whereas crosslinking dense ECM decreased invasiveness [89].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
“…A landmark study by the Weaver group showed that collagen crosslinking-induced ECM stiffening supports the invasive phenotype by enhancing integrin signaling [78]. By using glutaraldehyde as a crosslinker to increase the stiffness of collagen gels independently from pore size or collagen concentration, Lang et al showed that 3D invasion is dependent on pore size; while increased matrix stiffness promotes 3D invasion in gels with large pores (small steric hindrance), increased matrix stiffness hinders cell invasion in gels with small pores (large steric hindrance) [79]. In another interesting study, the Weaver group reported the development of a 3D tension bioreactor platform to facilitate studies on ECM stiffness; by mechanically loading collagen gels to induce gel stiffening (via collagen strain hardening) while maintaining composition and pore size, increasing matrix stiffness was also found to enhance tumor cell invasion [80].…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%